Overview of night-time road construction activities : the factors, effect and safety measures / Abdul Muhaimin Ab Wahid ... [et al.] - Ab Wahid, Abdul Muhaimin; Abdul Tharim, Asniza Hamimi; Jaffar, Noraidawati; Kurdi, Mohd Khairi; Shuib, Mohamad Nasharudine; Azli, Mohd Syhidi; Ma’arof, Khairul Anuar; Yusof, Ismail (2012)
This paper gives an overview of night-time road construction activities. The objective is to give an idea on why road construction is conducted during night-time and its effects. This paper will include the criteria in determining whether to conduct road construction work at night-time or not. This paper will also look into details for implications that night-time construction will have on a project, namely in terms of safety, productivity, quality and welfare of workers. This paper will then study on how to avoid the negative impact of night-time road construction works, especially the safety impact through gathering and studying literatures.